Rancang Bangun Produk Ecostove “Jolseuneu” Sebagai Bentuk Pemanfaatan Limbah Minyak Jelantah di Kelurahan Cibaduyut Kidul - Muhammad Zidan Effendi; Deni Sutana; Adysti Maulin; Novi Suci Maharani; Syifa Aditya; Devi Elora (Jurnal Pengabdian Tri Bhakti, 2025)
This study aims to determine the design and implementation of the EcoStove "JOLseuneu" product as a form of utilization of household waste cooking oil (jelantah) in the Cibaduyut Kidul sub-district, Bojongloa Kidul district, Bandung City. This research is based on fieldwork because it involves tools and materials as well as socialization with the community. The results obtained indicate that the EcoStove "JOLseuneu" product is very easy to apply as an alternative stove and can provide a concrete solution for the utilization and management of used cooking oil waste, as well as a form of environmentally friendly fuel savings (biogas/biomass).